ANALISIS YURIDIS TERHADAP PERJANJIAN KERJA DALAM PERUSAHAAN PERKEBUNAN - Masitah pohan; Rahma Yanti (LPPM Universitas Putera Batam, 2020)
A balanced position between employers and workers in practice is very rarely fulfilled due to a number of welds and the reality encountered. In addition, equality of position between employers and workers is also not realized, if there is no equality of ability between the two parties. If the ability of the parties is not balanced, the conditions that occur are those who have, ability and strong capital, such as the employer will force his will on workers who have weak abilities and positions. The research objectives raised are First, To know about out workes/ laborer interv in the implementation of the work agreement. Second, To know about. Secound, To find out the arrangement of work agreements of future plantation companies based on a balanced bargaining position for the parties. The research method used in the preparation of this dissertation is to apply normative or doctrinal legal research, with comparative law analysis and study approaches by emphasizing comparisons with legal provisions governing work agreements in several common law and civil law countries, as the basis of methodology legal research. Data collection tools come from the study of documents on secondary data. The balanced position between workers and workers is certainly directly proportional to the protection of workers. For this reason, regulations are needed that can accommodate the interests of the parties concerned.